Diagnosis of lymph node tuberculosis using the GeneXpert MTB/RIF in Bangladesh (Mediscope, 2018)
The purpose of this study was to evaluate the accuracy of the GeneXpert M. tuberculosis (MTB)/ rifampicin (RIF) test for the detection of MTB in lymph node aspirated samples. This study was conducted in the Department of Pathology, Bangabandhu Sheikh Mujib Medical University, Bangladesh. This study was done during the period from July 2013 to May 2015. A total of 317 clinically suspected tuberculous lymphadenitis patients without malignancy were included in the study. The culture test and GeneXpert test were used for detection of MTB in lymph node aspirated material. Among the 317 samples tested, the GeneXpert detected the DNA of MTB in 167 samples (52.7%), whereas culture test was positive in 74 (23.3%) specimens. GeneXpert also detected 8 RIF resistance cases. GeneXpert sensitivity and specificity results were assessed according to culture results. The sensitivity and specificity of the GeneXpert assay was 95.9% and 60.5%, respectively. The implementation of the GeneXpert MTB/RIF assay may dramatically improve the rapid diagnosis of lymph node TB. The GeneXpert MTB/RIF may replace usual conventional method like culture test for detection of MTB.Mediscope Vol. 6, No. 1: Jan 2019, Page 19-23